Utilização de fatores de produção na agricultura de subsistência: uma comparação entre duas regiões de Minas Gerais - Ferreira Pérez Menjívar , Rosaria M S; Moreira Leite , Carlos Antônio (Revista Ceres, 2025)
A comparative study was made of the use of production inputs of two groups of small farmers in «Zona da Mata» and «Nordeste de Minas in the State of Minas Gerais.